Antimicrobial and antitumor activities of 1, 2, 4‐triazoles/polypyrrole chitosan core shell nanoparticles. (27th April 2017) - Salahuddin, Nehal; Elbarbary, Ahmed A.; Salem, Mohamed L.; Elksass, Samar
Abstract: Combination of natural biodegradable polymer with a synthetic polymer offers excellent properties for the support in drug delivery system. For this purpose, biodegradable conductive nanoparticle polypyrrole based on chitosan (PPC) has been prepared via oxidative polymerization of pyrrole in presence of chitosan using FeCl3 as oxidant in acidic medium and used as a carrier for 1, 2, 4‐triazoles. The resultant nanoparticles were characterized by X‐ray diffraction, Fourier transform infrared analysis, transmission electron microscopy, scanning electron microscopy, and thermal gravimetric analysis. The results indicate that spherical nanoparticle of average diameter 52 ± 8 nm was successfully prepared. The spherical particles were composed of dark sphere surrounded by grey shell. A circumferential dark ring is observed in the shell after loading 1, 2, 4‐triazoles into PPC nanoparticles. The loaded triazoles were released almost linearly against time in a sustained fashion into different pH media. The mechanism of triazoles release was determined using different kinetics equations. The antibacterial activities against the gram‐negative and gram‐positive bacteria were examined. Furthermore, the antitumor activity of PPC nanoparticles loaded 1, 2, 4‐triazoles was also examined against Ehrlich ascites carcinoma cells and breast cancer cell line (MCF7). Polypyrrole chitosan loaded nanoparticles exhibited higher antitumor activity than 1, 2, 4‐triazoles. Abstract : The polypyrrole chitosan (PPC) nanoparticles have been prepared by in situ oxidative polymerization of pyrrole in chitosan solution using FeCl3 as an oxidant. 1, 2, 4‐Triazole derivatives (I‐IV) were loaded into PPC nanoparticles (PPCI, PPCII, PPCIII, and PPCIV). The antitumor activity of PPC nanoparticles loaded 1, 2, 4‐triazoles was examined against Ehrlich ascites carcinoma cells and breast cancer cell line (MCF7). PPCIV nanoparticles showed high efficacy against Ehrlich ascites carcinoma tumor cells in vitro.